Environmental preservation of emerging parabens contamination: effect of Ag and Pt loading over the catalytic efficiency of TiO2 during photocatalytic ozonation. (October 2017) - Gomes, J.; Lopes, A.; Bednarczyk, K.; Gmurek, M.; Stelmachowski, M.; Zaleska-Medynska, A.; Quinta-Ferreira, M.E.; Costa, R.; Quinta-Ferreira, R.M.; Martins, R.C.
Abstract: The aim of this study was to verify the effect of Ag and Pt with different loadings (0.1 and 0.5wt.%) as dopants on TiO2 for the degradation of a mixture of five parabens through photocatalytic ozonation. The effect of the treatment on the mixture toxicity over different species was also analyzed. The best catalyst in terms of parabens degradation was 0.5%Ag-TiO2 .The decrease of metal loading on TiO2 decreased the parabens degradation efficiency as well as COD and TOC removal. Also this decrease has a slight effect over the treated solution toxicity over the different species tested.